G-Calculus in Economic Growth Models: A Mathematical Framework - Kumar, Nand Kishor; Sahani, Suresh Kumar (Lembaga Yasin AlSys, 2025)
Economic growth models are essential for understanding the long-term dynamics of economies, yet traditional models often rely on classical differential and integral calculus, which may inadequately represent discrete, nonlinear, or growth-oriented phenomena. This study aims to introduce G-Calculus (Geometric Calculus), an extension of non-Newtonian calculus, as an alternative analytical framework that is particularly effective for modeling multiplicative and exponential growth systems. We present the theoretical underpinnings of G-Calculus and apply it to established economic growth frameworks, such as the Solow model and endogenous growth theory. By utilizing a comparative analysis, we evaluate the performance of G-Calculus in capturing economic dynamics, revealing significant advantages in terms of both accuracy and applicability. The findings indicate that G-Calculus provides a more natural and effective representation of economic growth processes, thereby enhancing the analytical capabilities of economists. This study contributes to the existing literature by offering a novel perspective on economic modeling, suggesting that G-Calculus can be a valuable tool for researchers and policymakers aiming to gain deeper insights into economic development.